Identifying and Treating Incarcerated Women Experiencing Substance Use Disorders: A Review - Staton M; Tillson M; Levi MM; Dickson M; Webster M; Leukefeld C (Dove Medical Press, 2023)
Michele Staton,1,2 Martha Tillson,2 Mary M Levi,3 Megan Dickson,1,2 Matt Webster,1,2 Carl Leukefeld1,2 1Department of Behavioral Science, University of Kentucky, Lexington, KY, USA; 2Center on Drug and Alcohol Research, University of Kentucky, Lexington, KY, USA; 3Department of Psychology, University of Kentucky, Lexington, KY, USACorrespondence: Michele Staton, University of Kentucky, 117 Medical Behavioral Science Building, Lexington, KY, 40506, USA, Tel +1-859-257-2483, Email mstaton@uky.eduAbstract: While research on substance use disorder (SUD) treatment among justice-involved populations has grown in recent years, the majority of corrections-based SUD studies have predominantly included incarcerated men or men on community supervision. This review 1) highlights special considerations for incarcerated women that may serve as facilitating factors or barriers to SUD treatment; 2) describes selected evidence-based practices for women along the cascade of care for SUD including screening and assessment, treatment and intervention strategies, and referral to services during community re-entry; and 3) discusses conclusions and implications for SUD treatment for incarcerated women.Keywords: incarcerated women, SUD, treatment, justice-involvement